Direct Oral Anticoagulants for the Treatment of Venous Thromboembolism in Japan - Nakamura, Mashio (J Atheroscler Thromb, 2017)
Direct oral anticoagulants (DOACs) were developed to compensate for the demerits of warfarin. In Japan, three factor Xa inhibitors are used for the treatment of venous thromboembolism (VTE): edoxaban, rivaroxaban, and apixaban. Despite problems, such as the inability to monitor their effect and the lack of an antidote, these inhibitors have the same efficacy as conventional treatment with warfarin, and they are associated with a significantly high degree of safety in relation to hemorrhagic complications. East Asians, including Japanese, suffer from hemorrhage more frequently; therefore, DOACs are considered to be highly effective. Although there is no evidence to date, DOACs may be effective in a wide variety of ways, including the possibility that they prevent recurrence over the long term, reduce the length of hospitalization, allow treatment to be started on an outpatient basis, and be effective in cancer patients.